2010
DOI: 10.1002/lary.21101
|View full text |Cite
|
Sign up to set email alerts
|

Exostoses of the paranasal sinuses

Abstract: While bony exostoses of the external auditory canal have long been recognized as a complication of cold-water swimming, bony exostoses of the paranasal sinuses have not been previously reported. We present an unusual case of multiple exostoses of the paranasal sinuses, which began coincident with nasal irrigation with cold gentamicin solution. The patient had had prior endoscopic sinus surgery. Topical antibiotic gentamicin irrigation lessened recurrence of bacterial sinus episodes. He admitted to using the ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 6 publications
0
18
1
3
Order By: Relevance
“…The ability of exostoses to occur within the paranasal sinuses was only recently reported 6. Literature on the topic is still limited to the index case report first noting its occurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of exostoses to occur within the paranasal sinuses was only recently reported 6. Literature on the topic is still limited to the index case report first noting its occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Paranasal sinus exostosis (PSE) is a new diagnostic entity that appears to be a complication of nasal irrigations performed with cold solutions. To date, there has been only one case of exostoses involving the paranasal sinuses,6 observed in a CRS patient irrigating with cold gentamicin, reported in the otolaryngology literature. The purpose of this study was to report our experience with PSE and further characterize this unusual condition.…”
Section: Introductionmentioning
confidence: 99%
“…Exostoses in the paranasal sinuses have been reported several times in the otolaryngology literature, but have not been described in the radiology literature to our knowledge [5-7]. The objective of this paper is to describe the CT features of this unusual entity, presumably related to chronic sinonasal irrigation.…”
Section: Introductionmentioning
confidence: 99%
“…22 Some authors have reported cases of exostoses in patients undergoing nasal irrigation therapy, thus correlating a cold temperature with a possible onset of exostosis. 23 The etiology and mechanisms of oral exostoses are unclear and there is no consensus among the investigators. Various authors have suggested several etiological factors such as genetic traits, en-vironmental factors, mastication and occlusal stress, inflammation, systemic diseases, and the post-menopausal period.…”
Section: Introductionmentioning
confidence: 99%
“…This article aims at describing an idiopathic and rare case of bilateral exostosis obtained by cone beam computed tomography-CBCT. 1,12,23,24,25…”
Section: Introductionmentioning
confidence: 99%